Effects of curcumin supplementation on insomnia and daytime sleepiness in young women with premenstrual syndrome and dysmenorrhea: A randomized clinical trial - Saman Seyedabadi; Zahra Sadat Hoseini; Gordon A. Ferns; Afsane Bahrami (Mashhad University of Medical Sciences, 2023)
Objective: Premenstrual syndrome and primary dysmenorrhea are common gynecological complaints that are associated with psychological disorders. There is increasing evidence for the neuroprotective properties of curcumin, a polyphenolic natural product. This study aimed to assess the effects of curcumin on sleep complications in women with premenstrual syndrome and dysmenorrhea.Materials and Methods: This triple-masked, placebo-controlled clinical trial comprised 124 patients with both premenstrual syndrome and dysmenorrhea. Participants were randomly assigned to curcumin (n=57) or control (n=60) groups. Each participant received one capsule containing either 500 mg of curcumin plus piperine or placebo, daily, from 7 days before until 3 days after menstruation for three consecutive menstrual cycles. Insomnia and sleepiness were assessed using standard questionnaires.Results: Scores for insomnia and daytime sleepiness were directly correlated with the Premenstrual Syndrome Screening Tool (PSST) score (p<0.05), but not with the visual analogue scale (VAS) score at baseline (p>0.05). There was a non-significant reduction in insomnia and sleepiness scores in both curcumin and placebo groups after the study intervention. Whilst, improvement rate of insomnia status, daytime sleepiness severity, short sleep duration and difficult sleep initiation was not statistically significant between the curcumin and placebo groups.Conclusion: Curcumin does not significantly affect sleep disorders in young women with premenstrual syndrome and dysmenorrhea.